Safety culture in the maternity units: a census survey using the safety attitudes questionnaire - Savva, Nicos; Papadopoulou, Maria; Raftopoulos, Vasilios (My University, 2011)
Background: Patient safety has been a priority for many societies and health care systems in the last decades. Identification of preventable risks and aversion of potentially unsafe situations and fatal complications in maternity units is life saving. The explicit need to focus on quality of care underpins the aim of the study to initially evaluate the safety culture and teamwork climate in the public Maternity Units of the 5 Regional Hospitals in Cyprus as measured by a validated safety attitudes tool. Methods. Data were collected from 140 midwives working in the public sector all over Cyprus by the Greek Version of the Safety Attitudes Questionnaire-Labor version. Results: One hundred and six (75.71%) registered midwives completed the questionnaire fully. The median of total work experience as a registered midwife was 3 years (IQR: 2-18.25); whereas the median of total working experience in the nursing and maternity units was 5 years (IQR: 2-21.75). Experienced midwives rated the following domains higher: team work, safety climate, job satisfaction and working conditions as opposed to the midwives with less experience. Additionally those with a longer working life in the current maternity units rated these domains higher: safety climate, job satisfaction and working conditions as opposed to the less experienced midwives. Conclusions: The high mean total score on team work and safety climate in the more experienced group of midwives is a predominant finding for the maternity units of Cyprus. In Cyprus where facilities are small in size and midwives know each other, share more responsibility towards patient safety. It could be suggested that younger midwives need more support and teamwork practice to enhance the safety and teamwork climate towards self-confidence.
Keywords: Maternity care; Patient safety; Quality care; Safety attitudes; Safety culture